2007
DOI: 10.5465/amr.2007.24351846
|View full text |Cite
|
Sign up to set email alerts
|

Motivation to Lead, Motivation to Follow: The Role of the Self-Regulatory Focus in Leadership Processes

Abstract: DINA VAN DIJK Ben-Gurion University of the Negev In this paper we integrate recent theories of motivation and leadership. Drawing on the self-regulatory focus theory and on self-concept based theories of leadership, we develop a conceptual framework proposing that leaders' chronic self-regulatory focus (promotion versus prevention), in conjunction with their values, influences their motivation to lead and, subsequently, their leadership behavior. We further suggest that leaders may influence the motivational s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
604
2
13

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 630 publications
(635 citation statements)
references
References 98 publications
(206 reference statements)
16
604
2
13
Order By: Relevance
“…Drawing on the self-regulatory focus theory and on self-concept based theories of leadership, Kark and Van Dijk (2007) developed a conceptual framework proposing that individuals' promotion foci, which represents the "ideal self" and focuses individuals and groups on their hopes, wishes, and aspirations, is likely to moderate the relationship between transformational leadership and creativity. In contrast, transactional and monitoring leadership is likely to enhance followers' prevention self-regulatory foci, which represents the "ought self" and focuses individuals and groups on their duties, obligations, and responsibilities and is likely to limit creativity at the individual and team level.…”
Section: Individual Level Studiesmentioning
confidence: 99%
“…Drawing on the self-regulatory focus theory and on self-concept based theories of leadership, Kark and Van Dijk (2007) developed a conceptual framework proposing that individuals' promotion foci, which represents the "ideal self" and focuses individuals and groups on their hopes, wishes, and aspirations, is likely to moderate the relationship between transformational leadership and creativity. In contrast, transactional and monitoring leadership is likely to enhance followers' prevention self-regulatory foci, which represents the "ought self" and focuses individuals and groups on their duties, obligations, and responsibilities and is likely to limit creativity at the individual and team level.…”
Section: Individual Level Studiesmentioning
confidence: 99%
“…From the findings above, this study can be concluded as follows: First of all, exporters emphasizing on prevention focus -which tend to be "risk-averse", concerned with duties and obligations, are likely to be sensitive to the presence or absence of punishments, and use avoidance as a goal attainment strategy -and exporters emphasizing on promotion FourA 2016 13001 (2017) focus, which is wanting to benefit from high energy and to develop the advantage of creative behaviors [9,10], will have intention to form relationships with their partners, produce some innovation, increase the export performances, and develop its absorptive capacity at the same time. Secondly, it is important for exporters to have customer orientation or competitor orientation simultaneously.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, exporters with stronger chronic prevention focus are more to be "risk-averse" [8,11]. Furthermore, the purpose of the prevention focus is wanting to avoid the chance of illness or assure their safety and security, to maintain routines, and to preserve the status quo [9,10]. Therefore, these exporters will have intention to form relationships with their partners, produce some innovation, increasing the export performances, and developing its absorptive capacity at the same time.…”
Section: The Effect Of Regulatory Focusmentioning
confidence: 99%
See 1 more Smart Citation
“…support from major users and other agents) for the development of the new technology. Evidence from the literature [17] suggested that senior management can be role models and their behaviour and statements can strongly shape employees' beliefs about what is important for the organisation [29,30]. Therefore, ensuring the necessary resources are provided for the development of the technology will indicate the importance of the project for the entire organisation.…”
Section: Significant Input From Production Personnelmentioning
confidence: 99%